Archangel's sun - Singh, Nalini, 1977- (Singh, Nalini, 1977- Guild Hunter series, 2020)
Titus, the archangel of Africa, must stop the reborn, rotting creatures that have gained vicious intelligence, from spreading across the world and asks the Hummingbird, an old and powerful woman who is his only hope, to stand by his side.